Centella asiatica L. Urban protects against cognitive dysfunction in alluminum chloride-induced neurotoxicity in rats via inhibition of acetylcholinesterase level. Issue 1 (31st December 2022) - Farhani, Nur Izzaty Binti Rosli; Chiroma, Samaila Musa; Mohamad, Tengku Azam Shah Tengku; Mohd Moklas, Mohamad Aris
ABSTRACT: Aluminum (Al) is a ubiquitous element on planet earth and its exposure to human systems is increasing steadily due to industrialization. Its accumulation in the biological systems have deleterious effects such as neurodegeneration and cognitive impairment. Centella asiatica L. (CA) is a herb used in the Ayurveda system of medicine as a neurotonic and for enhancement of memory. This study aimed at assessing the protective role of CA in aluminum chloride (AlCl3 ) induced cognitive dysfunction in rats. Results have shown that AlCl3 toxicity caused significant (p < 0.05) cognitive dysfunction of both spatial and non-spatial memory in rats, histopathological aberration of cerebral cortex and significant (p < 0.05) increase in the level of acetylcholinesterase in their brain. However, administration of CA irrespective of the dose given prevented all the observed changes which are comparable to a standard drug donepezil. CA prevented cognitive impairment and neurodegeneration in rats by decreasing the level of acetylcholinesterase. Hence, CA could be developed as a memory enhancing drug. Graphical abstract: uf0001